Take what you need : a novel - Novey, Idra (Viking, 2023)
"From award-winning novelist Idra Novey comes a "deft and surprising novel" with two unforgettable female voices. (Rumaan Alam) Set in the Allegheny Mountains of Pennsylvania, Take What You Need follows the estrangement and reconciliation of stepmother and daughter, Jean and Leah. Leah always felt her path diverged from Jean's and left her hometown without looking back, making a life for herself in the city as a young mother and academic. Now that Jean's gone, Leah must return to sort through all Jean has left behind. What she wasn't expecting to find was Jean's studio filled with metal sculptures born from the scraps of Pennsylvania's industrial history - its beauty challenging all she had initially thought of her hometown, and her own skepticism for why Jean had held onto to it so dearly. Told in alternating points of view, Take What You Need is a refreshing portrait of complex and resilient family relationships, and ultimately challenges our ideas about success in order to reaffirm values we all hold dear: beauty, hope, and family"--